Changing Leadership and Culture through Digital Technology at Snowpeak in Japan during the Covid-19 Global Pandemic - Dorin MARCHIS; Nitin HINGARH; Hirotoshi SATO; Cristian VLAD; Marius PROFIROIU (Revista de Management Comparat International)
This main intent of this research is to illustrate how Snow Peak, a global outdoors retailer headquartered in Japan, utilized modern technology to revamp people operations, culture and leadership during the Covid-19 global pandemic. It also provides insights into how traditional organizations can employ agile practices and other advanced people operations and communications initiatives to activate inclusion and provide opportunities for organizational transformation and business growth. The researchers analyzed multiple factors of impact which influenced culture, legacy business practices, work arrangements and digital technology adoption leading to the creation of a modern business architecture and organizational resilience, with a new, inclusive and people-focused style of leadership, needed to operate business through challenging times and unforeseen circumstances.